Can ChatGPT be guide in pediatric dentistry? - Canan Bayraktar Nahir (BMC Oral Health)
Abstract Background The use of ChatGPT in the field of health has recently gained popularity. In the field of dentistry, ChatGPT can provide services in areas such as, dental education and patient education. The aim of this study was to evaluate the quality, readability and originality of pediatric patient/parent information and academic content produced by ChatGPT in the field of pediatric dentistry. Methods A total of 60 questions were asked to ChatGPT for each topic (dental trauma, fluoride, and tooth eruption/oral health) consisting of pediatric patient/parent questions and academic questions. The modified Global Quality Scale (the scoring ranges from 1: poor quality to 5: excellent quality) was used to evaluate the quality of the answers and Flesch Reading Ease and Flesch-Kincaid Grade Level were used to evaluate the readability. A similarity index was used to compare the quantitative similarity of the answers given by the software with the guidelines and academic references in different databases. Results The evaluation of answers quality revealed an average score of 4.3 ± 0.7 for pediatric patient/parent questions and 3.7 ± 0.8 for academic questions, indicating a statistically significant difference (p < 0.05). Academic questions regarding dental trauma received the lowest scores (p < 0.05). However, no significant differences were observed in readability and similarity between ChatGPT answers for different question groups and topics (p > 0.05). Conclusions In pediatric dentistry, ChatGPT provides quality information to patients/parents. ChatGPT, which is difficult to readability for patients/parents and offers an acceptable similarity rate, needs to be improved in order to interact with people more efficiently and fluently.